The "Race" Toward Diversity, Inclusion, and Equity in Pathology: The Johns Hopkins Experience - Alisha D. Ware MD; Tricia Murdock MD; Lysandra Voltaggio MD; Annika L. Windon MD; Juan C. Troncoso MD; Ralph H. Hruban MD; Marissa J. White MD (Elsevier, 2019)
With 3.8% black trainees in 2012, pathology had significantly fewer trainees from groups underrepresented in medicine compared to other specialties. To address this, faculty in the Johns Hopkins Department of Pathology established an outreach program and funded rotation for students underrepresented in medicine and from disadvantaged groups. The aims were to increase exposure to the field and improve diversity, inclusion, and equity in pathology. A 1-month rotation for students underrepresented in medicine was established in 2013. Rotation schedules tailored to each rotator's interests included resident conferences and individual faculty meetings. In 2016, a proactive outreach program was established. Faculty visited historically black medical schools and underrepresented in medicine student groups at other institutions, where they gave a "Careers in Pathology" presentation targeted to second- and third-year medical students. Faculty also attended underrepresented in medicine student conferences and participated in high school student programs to further expand the underrepresented in medicine pipeline into medicine and pathology. Since 2016, fourteen outreach presentations have been delivered. The number of rotators increased from 1 in 2013 to 18 in July 2019. Rotators self-identified as African, African American, Hispanic, and Native American. Most were second- to fourth-year medical students, and 1 was a pathology resident. Six rotators are currently pathology residents, and others are strongly considering applying to pathology. The outreach efforts account for the success of our rotation, which, in turn, has had a positive impact on interest in pathology. However, we recognize barriers to retention and intend to incorporate additional professional development activities to further address equity.